"Going Solo" or Joining Gangs while Doing Time: Perceptions of Prison Gangs among the Formerly Incarcerated. (2nd July 2020) - Paat, Yok-Fong; Hernandez, Eddie; Hope, Trina L.; Muñoz, Jennifer; Zamora, Hector; Sanchez, Michael H.; Contreras, Sonny
Abstract: Using in-depth, face-to-face personal interviews of 25 formerly incarcerated participants, this study examines former inmates' perceptions of prison gang affiliation, factors that shaped their decision to join, associate, and disengage from prison gangs, as well as the impact of gang involvement on their imprisonment adaptation. Overall, we found that inmates' decisions about gang affiliation were linked to a variety of considerations – from personal safety, a sense of pride/belonging, to the consequences of gang affiliation for the prospect of release. Based on the narratives from our participants, two key themes emerge – contextual effects and individual selection effects, each with different policy implications. Findings from this study can be used to develop and improve research instruments for larger scale quantitative and qualitative studies to further understand the experiences of gang affiliated inmates.